Infection control risk assessment (ICRA) in the isolation room of the respira lung hospital Yogyakarta - Purwanto Purwanto; Kusbaryanto Kusbaryanto (Universitas Aisyah Pringsewu, 2023)
Infectious diseases are still a world health problem, including Indonesia. The incidence of Healthcare Associated Infections (HAIs) in the world is still high, not only in America but also in Europe and low- and middle-income countries. Healthcare Associated Infections (HAIs) can be prevented and controlled by implementing infection prevention and control. Infection Control Risk Assessment (ICRA) is a process to assess the implementation of infection prevention and control in health care facilities so as to describe the level of infection risk. Isolation room is a room to treat infectious patients so that they do not spread or spread to officers, visitors or other patients. This study aims to determine the risk of infection in the isolation room of Respira Lung Hospital measured using ICRA instruments from the CDC (Centers for Disease Control and Prevention). This research uses the Mix Method method, a combination of quantitative, descriptive and qualitative. The suitability of ICRA instruments with isolation chambers reached 65.3%. While the assessment of infrastructure facilities is 81% and the assessment for programs and competencies is 57.4%. Thus, overall infection risk control in the isolation room is quite good (69.2%), indicating that the risk of infection in the isolation room of Respira Lung Hospital is included in the medium risk category.Abstrak: Infectious diseases are still a world health problem, including Indonesia. The incidence of Healthcare Associated Infections (HAIs) in the world is still high, not only in America but also in Europe and low- and middle-income countries. Healthcare Associated Infections (HAIs) can be prevented and controlled by implementing infection prevention and control. Infection Control Risk Assessment (ICRA) is a process to assess the implementation of infection prevention and control in health care facilities so as to describe the level of infection risk. Isolation room is a room to treat infectious patients so that they do not spread or spread to officers, visitors or other patients. This study aims to determine the risk of infection in the isolation room of Respira Lung Hospital measured using ICRA instruments from the CDC (Centers for Disease Control and Prevention). This research uses the Mix Method method, a combination of quantitative, descriptive and qualitative. The suitability of ICRA instruments with isolation chambers reached 65.3%. While the assessment of infrastructure facilities is 81% and the assessment for programs and competencies is 57.4%. Thus, overall infection risk control in the isolation room is quite good (69.2%), indicating that the risk of infection in the isolation room of Respira Lung Hospital is included in the medium risk category.